A sodium ion battery positive electrode material and preparation method thereof and a sodium ion battery
By doping transition metal and sodium-position elements into the positive electrode material of the sodium ion battery and forming a cladding layer, adjusting the relationship between the peak strength ratio and unit cell volume of the material, the problems of high residual alkali, poor air stability and poor circulation performance of the material are solved, and the high capacity and long circulation performance are achieved.
Patent Information
- Application Number
- CN202510046040.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing sodium ion battery positive electrode materials have problems such as high residual alkali, poor air stability and poor circulation performance, and it is difficult to take into account both high capacity and long circulation performance.
By doping transition metals and sodium-position elements into the positive electrode material of the sodium-ion cell and forming a cladding layer on the surface of the material, the relationship between the peak strength ratio of the (003) crystal plane and the unit cell volume is adjusted to reduce cation mixing and improve layer spacing.
It effectively reduces the residual alkali content of the material, improves air stability and circulation performance, and enables the sodium ion battery positive electrode material to show optimal performance in the fields of energy storage and small power batteries.
Smart Images

Figure CN119447279B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery. Background Art
[0002] In recent years, with the development of new energy vehicles, the demand for lithium-ion batteries has increased dramatically, and the market demand has continued to expand. The production of lithium-ion batteries requires a large amount of raw materials such as lithium, cobalt, and nickel. With the rapid growth of demand for lithium-ion batteries, the supply of raw materials faces certain pressure. In addition, the limited reserves of lithium resources make the cost of lithium-ion batteries relatively high.
[0003] The metal resources needed for sodium-ion batteries are widely distributed and low-cost, so sodium-ion batteries have been vigorously developed in recent years. The positive electrode material is one of the main materials of sodium-ion batteries. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides, polyanions and Prussian blue positive electrode materials. Among them, polyanion positive electrode materials have low energy density due to low capacity, but their cycle performance is better, and they have great development in the field of energy storage applications. Due to the problem of preparation method, the crystal water inside Prussian blue materials is difficult to remove, and the safety performance of the battery is subject to certain restrictions. However, the layered oxide positive electrode material is highly compatible with the process and production equipment of lithium battery ternary positive electrode materials, and is widely regarded as the first sodium positive electrode material to achieve large-scale mass production. Sodium layered oxide positive electrode materials have the characteristics of good rate performance, good low-temperature performance, relatively high capacity, and convenient synthesis. They are mainly used in the field of energy storage and small power batteries, but sodium layered oxide materials have the problem that it is difficult to take both high capacity and long cycle performance into account, and the residual alkali content of the material is high, which affects the electrical properties of sodium layered oxide positive electrode materials.
[0004] In addition, layered oxide positive electrode materials also have their own technical development bottlenecks. For example, because the raw materials used are sodium carbonate or sodium hydroxide, the activity of sodium is higher than that of lithium, which inevitably causes high residual alkali in the positive electrode material during the preparation process. It is easy to cause the slurry to jelly during the homogenization process. This phenomenon has become the main influencing factor of battery gas production. The second aspect is that the air stability of layered oxides is poor. The positive electrode materials must be stored or vacuum packaged under low air humidity, which increases the storage and transportation costs of the materials. Finally, the cycle performance of layered oxides is poor. During the charge and discharge process, the layered structure is prone to phase change, resulting in a decrease in the structural stability of the material and affecting the cycle life of the battery. When some materials are charged and discharged in high-voltage areas, oxygen is easily irreversibly released, further reducing the stability of the material.
[0005] Although the prior art performs ion doping and inert coating on layered oxides, it still cannot effectively improve the problems of high residual alkali, poor air stability and poor cycle of the positive electrode material.
[0006] Based on the above research, it is necessary to provide a sodium ion battery positive electrode material, which has the characteristics of low residual alkali content, high air stability and excellent cycle performance. Summary of the invention
[0007] The object of the present invention is to provide a sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery. The sodium ion battery positive electrode material satisfies a specific relationship between the peak intensity ratio of the (003) crystal plane and the (104) crystal plane and the positive electrode material unit cell volume V, thereby ensuring the basic parameters of the sodium ion positive electrode product material, reducing the mixing phenomenon and improving the problem of small interlayer spacing, thereby effectively ensuring that the sodium ion battery positive electrode material exerts the best performance.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material comprises a transition metal doping element, a sodium doping element and a coating element;
[0010] The I(003) / I(104) of the sodium ion battery positive electrode material and the unit cell volume V of the sodium ion battery positive electrode material satisfy the following relationship:
[0011] 14≤I(003) / I(104)×V 1 / 2 ≤22.
[0012] The I(003) / I(104) of the sodium ion battery positive electrode material of the present invention and the unit cell volume V of the sodium ion battery positive electrode material satisfy a specific relationship because the peak intensity ratio of the (003) crystal plane and the (104) crystal plane represents the degree of cation mixing. The smaller the peak intensity ratio, the greater the mixing. In the sodium ion battery positive electrode material, the radius of sodium ions is 97pm, the radius of iron ions is 64pm, and the radius of nickel ions is 69pm. In addition, the migration energy barrier of nickel ions and iron ions is very low, so cation mixing is easy to occur during the preparation process; and the unit cell volume is a basic parameter of the material. The unit cell volume can roughly know the size of the lattice constants a, b and c, and can also indicate the size of the interlayer spacing. When the interlayer spacing is small, sodium ion deintercalation is more difficult and the capacity is low. When the interlayer spacing is large, sodium ion migration will be relatively easy, but cation mixing is also easy to occur. Therefore, it is necessary to define the relationship between I(003) / I(104) and V to satisfy the characteristics. The I(003) / I(104) of the sodium ion battery positive electrode material of the present invention and the unit cell volume V of the sodium ion battery positive electrode material satisfy a specific relationship to ensure the basic parameters of the sodium ion battery positive electrode material and ensure that the sodium ion battery positive electrode material exerts the best performance. If I(003) / I(104)×V1 / 2 Outside the required range, it indicates that the cation mixing of the material is serious, or the interlayer spacing is small, resulting in low product capacity and poor cycle. The sodium ion battery positive electrode material of the present invention is doped at the transition metal position and the sodium position at the same time. After the inactive element is doped into the transition metal layer, it can form a specific chemical bond with the transition metal to inhibit the occurrence of lattice distortion and phase change. At the same time, doping at the sodium position can regulate the deintercalation behavior of sodium ions and reduce the damage to the structure during the deintercalation process of sodium ions. The synergistic effect of the two can effectively improve the structural stability of the material, inhibit harmful phase changes, and improve the cycle performance of the battery.
[0013] The sodium ion battery positive electrode material of the present invention also contains a coating layer, and the coating element is located in the coating layer. The coating layer can improve the performance of the positive electrode material through physical barrier and chemical stability, and can also affect the diffusion behavior of sodium ions to a certain extent. By optimizing the thickness and properties of the coating layer, the adsorption and diffusion efficiency of sodium ions on the surface of the material can be improved. In addition, the coating layer can react with the residual alkali (sodium carbonate, sodium bicarbonate and sodium hydroxide) on the surface of the first-fired material during the secondary sintering process, consume the residual alkali on the surface of the positive electrode material, achieve the effect of reducing the residual alkali, improve the slurry stability of the material in the battery manufacturing stage, and reduce the gas production of the battery.
[0014] 14≤I(003) / I(104)×V 1 / 2 ≤22, for example, it can be 14, 15, 16, 17, 18, 19, 20, 21 or 22, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] The unit of V in the present invention is Å 3 , 14≤I(003) / I(104)×V 1 / 2 ≤22 refers to I(003) / I(104)×V 1 / 2 The obtained values satisfy this relationship.
[0016] The I(003) / I(104) is ≥ 1.2, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5, 122Å 3 ≤V≤128Å 3 , for example, it could be 122 Å 3 , 123Å 3 , 124Å 3 , 125Å 3 , 126Å 3 , 127Å 3 or 128 Å 3, but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0017] The present invention preferably has I(003) / I(104) and V in the above range, which can promote I(003) / I(104)×V 1 / 2 Satisfying a specific relationship reduces the mixing of cations and increases the interlayer spacing.
[0018] Preferably, the internal high-nickel ternary nickel-iron-manganese precursor accounts for 60-70wt% of the entire precursor material, for example, it can be 60%, 65% or 60%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the sodium ion battery positive electrode material and the precursor material for preparing the sodium ion battery positive electrode material satisfy the following relationship:
[0020] 10≤D2 / D1+B1×B2≤28, for example, it can be 10, 12, 14, 16, 18, 20, 22, 24, 26 or 28, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Among them, D1 is the particle size D50 of the precursor material for preparing the sodium ion battery positive electrode material, B1 is the specific surface area of the precursor material for preparing the sodium ion battery positive electrode material, D2 is the particle size D50 of the sodium ion battery positive electrode material, and B2 is the specific surface area of the sodium ion battery positive electrode material.
[0022] The particle size and specific surface area of the precursor material of the present invention have an important influence on the performance of the positive electrode material. The smaller precursor particle size can increase the reaction area of the material, thereby improving the rate performance of the battery. However, too small a particle size may also cause the material structure to be unstable, increase the tendency to agglomerate, and affect the consistency of the material. A higher specific surface area can increase the contact area with the electrolyte, which helps to improve the discharge capacity and rate performance of the battery. However, too high a specific surface area may also increase the side reactions of the material and the electrolyte, affecting the cycle life. Therefore, by controlling the specific surface area and particle size of the precursor, the positive electrode material is achieved to have a suitable specific surface area and particle size, and then the electrochemical properties of the positive electrode material can be effectively controlled, and the suitable specific surface area and particle size of the positive electrode material can also affect the positive electrode material crystal structure, thereby controlling the internal crystal parameter performance of the material through the apparent physical and chemical properties, and achieving the purpose of effectively improving the performance of the positive electrode material of the sodium ion battery.
[0023] The units of D1 and D2 in the present invention are both μm, and the units of B1 and B2 are both m. 2 / g, and the above 10≤D2 / D1+B1×B2≤28 means that the value calculated by D2 / D1+B1×B2 satisfies the relationship.
[0024] The D1 is 3.0-7.0 μm, for example, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm or 7.0 μm, and the B1 is 25-50 μm. 2 / g, for example, it can be 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g or 50m 2 / g, the D2 is 5.0-10.0 μm, for example, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm or 10.0 μm, and the B2 is 0.3-0.7 μm 2 / g, for example, it can be 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g or 0.7m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the precursor materials for preparing the sodium ion battery positive electrode material include a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside.
[0026] The precursor material for preparing the sodium ion battery positive electrode material of the present invention comprises a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside, so that the positive electrode material is a ternary nickel-iron-manganese with high nickel content inside and a quaternary nickel-iron-manganese-copper positive electrode material with low nickel content and high copper content outside. The ternary nickel-iron-manganese positive electrode with high nickel concentration inside can provide a higher specific capacity, and the quaternary nickel-iron-manganese-copper positive electrode with high copper concentration outside can improve the stability of the material surface, which is beneficial to improving the cycle and rate performance of the battery, while improving the safety of the battery.
[0027] Preferably, the tap density of the precursor material for preparing the sodium ion battery positive electrode material is T1, and T1 is 1.0-1.6 g / cm 3 , for example, it can be 1.0 g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3or 1.6 g / cm 3 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0028] Preferably, the tap density of the sodium ion battery positive electrode material is T2, and T2 is 1.9-2.3 g / cm 3 , for example, it can be 1.9 g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 or 2.3g / cm 3 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0029] Preferably, the chemical formula of the precursor material for preparing the sodium ion battery positive electrode material is Ni x Fe y Mn z Cu 1-x-y-z (OH)2 or Ni x Fe y Mn z Cu 1-x-y-z CO2, wherein 0.2≤x≤0.3, for example, it can be 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3, 0.3≤y≤0.4, for example, it can be 0.3, 0.32, 0.34, 0.36, 0.38 or 0.4, 0.3≤z≤0.4, for example, it can be 0.3, 0.32, 0.34, 0.36, 0.38 or 0.4, 0.85≤x+y+z≤0.95, for example, it can be 0.85, 0.87, 0.89, 0.91, 0.93 or 0.95, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] The chemical formula of the ternary nickel-iron-manganese precursor with high internal nickel is Ni a Fe b Mn 1-a-b (OH)2 or Ni a Fe b Mn 1-a-b CO2, 0.21≤a≤0.4, for example, it can be 0.21, 0.25, 0.3, 0.35 or 0.4, 0.32≤b≤0.45, for example, it can be 0.32, 0.35, 0.4 or 0.45, the chemical formula of the quaternary nickel-iron-manganese-copper precursor with low nickel and high copper outside is Ni c Fe d Mn e Cu 1-c-d-e (OH)2 or Ni c Fed Mn e Cu 1-c-d-e CO2, wherein 0.15≤c≤0.32, for example, it can be 0.15, 0.2, 0.25, 0.3 or 0.32, 0.25≤d≤0.35, for example, it can be 0.25, 0.3 or 0.35, 0.25≤e≤0.35, for example, it can be 0.25, 0.30 or 0.35, 0.11≤c+d+e≤0.40, for example, it can be 0.11, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the transition metal doping element includes any one of Al, Y, Ti, Ta, Zn, Zr, Sr, Sb, W, Mo, Nb or Co, or a combination of at least two thereof.
[0032] Preferably, the sodium-site doping element includes any one of Li, K, Ca, Mg, B or Sc, or a combination of at least two of them.
[0033] Preferably, the coating element includes any one of Al, Y, Ti, Ta, Zn, Zr, Sr, Sb, W, Mo, Nb, Co, Ca, B or Mg, or a combination of at least two thereof.
[0034] In a second aspect, the present invention provides a method for preparing the positive electrode material for a sodium ion battery as described in the first aspect, the preparation method comprising the following steps:
[0035] (1) mixing a precursor material, a sodium source, a first dopant, and a second dopant once and sintering once to obtain a sintered material;
[0036] The first dopant includes a transition metal doping element, and the second dopant includes a sodium doping element;
[0037] (2) The calcined material and the coating agent in step (1) are mixed and sintered for a second time to obtain the positive electrode material for a sodium ion battery.
[0038] Preferably, the once-burned material in step (1) is also crushed before the secondary mixing.
[0039] Preferably, the amount of the first dopant added in step (1) is 1000-10000 ppm of the amount of the precursor material added, for example, it can be 1000 ppm, 3000 ppm, 5000 ppm, 7000 ppm, 9000 ppm or 10000 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, the amount of the second dopant added in step (1) is 500-5000 ppm of the amount of the precursor material added, for example, it can be 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm or 5000 ppm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the primary sintering temperature in step (1) is 850-1050°C, for example, 850°C, 950°C or 1050°C, and the sintering time is 10-14h, for example, 10h, 12h or 14h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, the primary sintering in step (1) is carried out in an air atmosphere with a flow rate of 15-25 L / min, for example, 15 L / min, 20 L / min or 25 L / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the method for preparing the precursor material in step (1) comprises the following steps:
[0044] The first mixed metal salt solution, the precipitant solution and the complexing agent solution are subjected to a first coprecipitation reaction, and after the first coprecipitation reaction is completed, the second mixed metal salt solution, the precipitant solution and the complexing agent solution are subjected to a second coprecipitation reaction to obtain the precursor material;
[0045] The first mixed metal salt solution includes Ni ions, Fe ions and Mn ions, and the second mixed metal salt solution includes Ni ions, Fe ions, Mn ions and Cu ions.
[0046] Preferably, when the amount of the first mixed metal salt solution added is 60-70% of the total amount, for example 60%, 65% or 70%, the first coprecipitation reaction is completed, and the copper salt solution is added to the remaining first mixed metal salt solution to obtain the second mixed metal salt solution.
[0047] Preferably, the concentration of the first mixed metal salt solution is 1-4 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L or 4 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the concentration of the copper salt solution is 1-2 mol / L, for example, 1 mol / L, 1.5 mol / L or 2 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the temperature of the first coprecipitation reaction and the second coprecipitation reaction are independently 40-70°C, for example, 40°C, 50°C, 60°C or 70°C, and the pH is independently 9-12, for example, 9, 10, 11 or 12, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the total time of the first coprecipitation reaction and the second coprecipitation reaction is 12-24h, for example, it can be 12h, 14h, 16h, 18h, 20h, 22h or 24h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] The post-treatment step of the precursor material of the present invention includes: filtering, washing and drying the precipitated product after the co-precipitation reaction, and then sieving it through a 300-400 mesh sieve (for example, 300 mesh, 350 mesh or 400 mesh).
[0052] Preferably, the amount of the coating agent added in step (2) is 1000-10000 ppm of the amount of the calcined material added, for example, it can be 1000 ppm, 3000 ppm, 5000 ppm, 7000 ppm, 9000 ppm or 10000 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] Preferably, the temperature of the secondary sintering in step (2) is 600-800°C, for example, 600°C, 700°C or 800°C, and the time is 8-12h, for example, 8h, 10h or 12h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0054] Preferably, the secondary sintering in step (2) is carried out in an air atmosphere with a flow rate of 15-25 L / min, for example, 15 L / min, 20 L / min or 25 L / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0055] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material as described in the first aspect.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The present invention ensures that the basic parameters of the positive electrode material of the sodium ion battery and the optimal performance of the positive electrode material of the sodium ion battery are ensured by making the I(003) / I(104) of the positive electrode material of the sodium ion battery and the unit cell volume V satisfy a specific relationship.1 / 2 Outside the required range, it indicates that the cation mixing of the material is serious or the interlayer spacing is small, which will result in low product capacity and poor circulation.
[0058] (2) The precursor material for preparing the sodium ion battery positive electrode material of the present invention includes a ternary nickel-iron-manganese precursor with a high internal nickel content, which can enable the positive electrode material to have a higher specific capacity and stability, which is beneficial to improving the battery's cycle and rate performance, while also improving the battery's safety.
[0059] (3) The doping of the sodium ion battery positive electrode material at different sites of the present invention can inhibit the occurrence of lattice distortion and phase change, regulate the sodium ion deintercalation behavior, effectively improve the structural stability of the material, inhibit harmful phase change, and improve the cycle performance of the battery; at the same time, the coating is used to improve the material stability, optimize the diffusion behavior of sodium ions, reduce the residual alkali content, and further improve the performance of the positive electrode material.
[0060] (4) The present invention achieves a specific relationship between the particle size and specific surface area of the precursor material and the particle size and specific surface area of the positive electrode material, so that the apparent physical and chemical properties can control the internal crystal parameter performance of the material, thereby achieving the purpose of effectively improving the performance of the positive electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is the first charge and discharge diagram of the battery prepared with the positive electrode materials described in Example 1 and Example 15 of the present invention;
[0062] Figure 2 This is a comparison chart of the cycle retention rates of batteries prepared from the positive electrode materials described in Example 1 and Example 15 of the present invention;
[0063] Figure 3 This is a comparison chart of the energy efficiency cycles of batteries prepared using the positive electrode materials described in Example 1 and Example 15 of the present invention. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Example 1
[0065] This embodiment provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material includes a transition metal doping element, a sodium doping element and a coating element, and I(003) / I(104) of the sodium ion battery positive electrode material and the unit cell volume V of the sodium ion battery positive electrode material satisfy the following relationship: 14≤I(003) / I(104)×V 1 / 2 ≤22;
[0066] The sodium ion battery positive electrode material and the precursor material for preparing the sodium ion battery positive electrode material satisfy the following relationship:
[0067] 10≤D2 / D1+B1×B2≤28;
[0068] Wherein, D1 is the particle size D50 of the precursor material for preparing the positive electrode material of the sodium ion battery, B1 is the specific surface area of the precursor material for preparing the positive electrode material of the sodium ion battery, D2 is the particle size D50 of the positive electrode material of the sodium ion battery, and B2 is the specific surface area of the positive electrode material of the sodium ion battery;
[0069] The precursor material for preparing the positive electrode material of the sodium ion battery includes a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside; the chemical formula of the precursor material for preparing the positive electrode material of the sodium ion battery is Ni 0.23 Fe 0.33 Mn 0.33 Cu 0.11 (OH)2;
[0070] The method for preparing the positive electrode material of a sodium ion battery comprises the following steps:
[0071] (1) preparing a mixed salt metal solution A with a total metal ion concentration of 3 mol / L according to the molar ratio of Ni, Fe and Mn of 26:37:37, preparing a metal salt solution B with a metal ion concentration of 1.5 mol / L, and preparing a sodium hydroxide solution and an ammonia solution;
[0072] Sodium hydroxide solution, ammonia solution and mixed metal salt solution A are respectively and simultaneously pumped into the reactor evenly and continuously, the temperature of the reaction system in the reactor is controlled to be 55° C. and the reaction pH is controlled to be 11, and a first coprecipitation reaction is performed;
[0073] (2) When the amount of the mixed metal salt solution A added is 2 / 3 of the total amount of the mixed metal salt solution A, the metal salt solution B is added to the remaining mixed metal salt solution A to form a mixed metal salt solution C with a molar ratio of Ni, Fe, Mn and Cu of 19:27:27:27, and then the sodium hydroxide solution, the ammonia solution and the mixed metal solution C are respectively and uniformly pumped dropwise into the reactor at the same time, the temperature of the reaction system in the reactor is controlled to be 55° C., the reaction pH is controlled to be 11, and a second coprecipitation reaction is carried out. The total time of the first coprecipitation reaction and the second coprecipitation reaction is 18 hours;
[0074] The precipitated product after the reaction is completed is filtered, washed and dried, and then sieved through a 350-mesh sieve to obtain the precursor material;
[0075] (3) The precursor material and sodium carbonate of step (2) are weighed separately according to a molar ratio of Me / Na=1.0 (Me is the total metal molar amount of the precursor material), and then a transition metal dopant and a sodium dopant are weighed. The doping amount of the transition metal dopant is 5000ppm of the amount of the precursor material added, and the doping amount of the sodium dopant is 800ppm of the amount of the precursor material added, wherein the transition metal dopant is Ti and the sodium dopant is Ca. Finally, the precursor material, sodium carbonate, the transition metal dopant and the sodium dopant are uniformly mixed using a high-speed mixer to obtain a once-mixed material;
[0076] (4) Sintering the mixed materials in a box furnace at a sintering temperature of 940°C for a holding time of 12 hours in an air atmosphere with a ventilation volume of 20 L / min to obtain a first-fired material, and crushing the first-mixed materials into single crystals using a jet mill to obtain a crushed material;
[0077] (5) The crushed material and the coating agent are uniformly mixed using a high-speed mixer, wherein the coating agent is Zr, and the coating amount is 6000ppm of the amount of the first-fired material added. The second-mixed material is sintered in a box furnace at a sintering temperature of 700°C, a holding time of 10 hours, an air atmosphere, and a ventilation volume of 20L / min to obtain the sodium ion battery positive electrode material. Example 2
[0078] This embodiment provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material includes a transition metal doping element, a sodium doping element and a coating element, and I(003) / I(104) of the sodium ion battery positive electrode material and the unit cell volume V of the sodium ion battery positive electrode material satisfy the following relationship: 14≤I(003) / I(104)×V 1 / 2 ≤22;
[0079] The sodium ion battery positive electrode material and the precursor material for preparing the sodium ion battery positive electrode material satisfy the following relationship:
[0080] 10≤D2 / D1+B1×B2≤28;
[0081] Wherein, D1 is the particle size D50 of the precursor material for preparing the positive electrode material of the sodium ion battery, B1 is the specific surface area of the precursor material for preparing the positive electrode material of the sodium ion battery, D2 is the particle size D50 of the positive electrode material of the sodium ion battery, and B2 is the specific surface area of the positive electrode material of the sodium ion battery;
[0082] The precursor material for preparing the positive electrode material of the sodium ion battery includes a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside; the chemical formula of the precursor material for preparing the positive electrode material of the sodium ion battery is Ni0.2 Fe 0.3 Mn 0.35 Cu 0.15 (OH)2;
[0083] The method for preparing the positive electrode material of a sodium ion battery comprises the following steps:
[0084] (1) preparing a mixed salt metal solution A with a total metal ion concentration of 1 mol / L according to the molar ratio of Ni, Fe and Mn of 24:35:41, preparing a metal salt solution B with a metal ion concentration of 2 mol / L, and preparing a sodium hydroxide solution and an ammonia solution;
[0085] Sodium hydroxide solution, ammonia solution and mixed metal salt solution A are respectively and simultaneously pumped into the reactor evenly and continuously, the temperature of the reaction system in the reactor is controlled to be 70° C. and the reaction pH is controlled to be 10, and a first coprecipitation reaction is performed;
[0086] (2) When the amount of the mixed metal salt solution A added is 60% of the total amount of the mixed metal salt solution A, the metal salt solution B is added to the remaining mixed metal salt solution A to form a mixed metal salt solution C with a molar ratio of Ni, Fe, Mn and Cu of 8:13:15:14, and then the sodium hydroxide solution, the ammonia solution and the mixed metal solution C are respectively and uniformly pumped dropwise into the reactor at the same time, the temperature of the reaction system in the reactor is controlled to 70°C, the reaction pH is controlled to 10, and a second coprecipitation reaction is carried out. The total time of the first coprecipitation reaction and the second coprecipitation reaction is 24 hours;
[0087] The precipitated product after the reaction is completed is filtered, washed and dried, and then sieved through a 300-mesh sieve to obtain the precursor material;
[0088] (3) The precursor material and sodium carbonate of step (2) are weighed separately according to a molar ratio of Me / Na=1.0 (Me is the total metal molar amount of the precursor material), and then a transition metal dopant and a sodium dopant are weighed. The doping amount of the transition metal dopant is 5000ppm of the amount of the precursor material added, and the doping amount of the sodium dopant is 500ppm of the amount of the precursor material added. The transition metal dopant is Y, and the sodium dopant is Mg. Finally, the precursor material, sodium carbonate, the transition metal dopant and the sodium dopant are uniformly mixed using a high-speed mixer to obtain a once-mixed material.
[0089] (4) Sintering the mixed materials in a box furnace at a sintering temperature of 850°C for a holding time of 14 hours in an air atmosphere with a ventilation volume of 25 L / min to obtain a first-fired material, and crushing the first-mixed materials into single crystals using a jet mill to obtain a crushed material;
[0090] (5) The crushed material and the coating agent are uniformly mixed using a high-speed mixer, wherein the coating agent is Ca, and the coating amount is 6000 ppm of the amount of the first-fired material added. The second-mixed material is sintered in a box furnace at a sintering temperature of 600° C., a holding time of 12 h, an air atmosphere, and a ventilation volume of 15 L / min to obtain the sodium ion battery positive electrode material. Example 3
[0091] This embodiment provides a sodium ion battery positive electrode material, the sodium ion battery positive electrode material includes a transition metal doping element, a sodium doping element and a coating element, and I(003) / I(104) of the sodium ion battery positive electrode material and the unit cell volume V of the sodium ion battery positive electrode material satisfy the following relationship: 14≤I(003) / I(104)×V 1 / 2 ≤22;
[0092] The sodium ion battery positive electrode material and the precursor material for preparing the sodium ion battery positive electrode material satisfy the following relationship:
[0093] 10≤D2 / D1+B1×B2≤28;
[0094] Wherein, D1 is the particle size D50 of the precursor material for preparing the positive electrode material of the sodium ion battery, B1 is the specific surface area of the precursor material for preparing the positive electrode material of the sodium ion battery, D2 is the particle size D50 of the positive electrode material of the sodium ion battery, and B2 is the specific surface area of the positive electrode material of the sodium ion battery;
[0095] The precursor material for preparing the positive electrode material of the sodium ion battery includes a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside; the chemical formula of the precursor material for preparing the positive electrode material of the sodium ion battery is Ni 0.3 Fe 0.35 Mn 0.3 Cu 0.05 (OH)2;
[0096] The method for preparing the positive electrode material of a sodium ion battery comprises the following steps:
[0097] (1) preparing a mixed salt metal solution A with a total metal ion concentration of 4 mol / L according to the molar ratio of Ni, Fe and Mn of 32:37:32, preparing a metal salt solution B with a metal ion concentration of 1 mol / L, and preparing a sodium hydroxide solution and an ammonia solution;
[0098] Sodium hydroxide solution, ammonia solution and mixed metal salt solution A are respectively and simultaneously pumped into the reactor evenly and continuously, the temperature of the reaction system in the reactor is controlled to be 50° C. and the reaction pH is controlled to be 12, and a first coprecipitation reaction is performed;
[0099] (2) When the amount of the mixed metal salt solution A added is 70% of the total amount of the mixed metal salt solution A, the metal salt solution B is added to the remaining mixed metal salt solution A to form a mixed metal salt solution C with a molar ratio of Ni, Fe, Mn and Cu of 26:32:28:13, and then the sodium hydroxide solution, the ammonia solution and the mixed metal solution C are respectively and uniformly pumped dropwise into the reactor at the same time, the temperature of the reaction system in the reactor is controlled to be 50°C, the reaction pH is controlled to be 12, and a second coprecipitation reaction is carried out. The total time of the first coprecipitation reaction and the second coprecipitation reaction is 12 hours;
[0100] The precipitated product after the reaction is completed is filtered, washed and dried, and then sieved through a 300-400 mesh sieve to obtain the precursor material;
[0101] (3) The precursor material and sodium carbonate of step (2) are weighed separately according to a molar ratio of Me / Na=1.0 (Me is the total metal molar amount of the precursor material), and then a transition metal dopant and a sodium dopant are weighed. The doping amount of the transition metal dopant is 5000ppm of the amount of the precursor material added, and the doping amount of the sodium dopant is 5000ppm of the amount of the precursor material added. The transition metal dopant is Al and Ti in a molar ratio of 1:1, and the sodium dopant is Ca and B in a molar ratio of 1:1. Finally, the precursor material, sodium carbonate, the transition metal dopant and the sodium dopant are uniformly mixed using a high-speed mixer to obtain a once-mixed material;
[0102] (4) Sintering the mixed materials in a box furnace at a sintering temperature of 1050°C for a holding time of 10 hours in an air atmosphere with a ventilation volume of 15 L / min to obtain a first-fired material, and crushing the first-mixed materials into single crystals using a jet mill to obtain a crushed material;
[0103] (5) The crushed material and the coating agent are uniformly mixed using a high-speed mixer, wherein the coating agent is Zn and Ca in a molar ratio of 1:1, and the coating amount is 6000 ppm of the amount of the first-fired material added. The second-mixed material is sintered in a box furnace at a sintering temperature of 800°C, a holding time of 8 hours, an air atmosphere, and a ventilation volume of 25 L / min to obtain the sodium ion battery positive electrode material.
[0104] Example 4 to Example 13 provide a sodium ion battery positive electrode material, which is the same as Example 1 except that the conditions in Table 1 are different from those in Example 1.
[0105] Example 14 provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material is different from Example 1 in the conditions in Table 1, and the chemical formula of the precursor material of Example 14 is Ni 0.23 Fe 0.33Mn 0.33 Cu 0.11 (OH)2 is a quaternary nickel-iron-manganese-copper material. The precursor prepared in Example 14 is directly prepared by coprecipitation reaction using mixed metal salt solution C.
[0106] Example 15 provides a sodium ion battery positive electrode material. The sodium ion battery positive electrode material is different from Example 1 in the conditions in Table 1. The chemical formula of the precursor material of Example 15 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 is a ternary nickel-iron-manganese material. In Example 15, when preparing the precursor, the mixed metal salt solution A is directly used to carry out the co-precipitation reaction. Except that the mixed metal salt solution C is not used for the co-precipitation reaction, the rest is the same as Example 1.
[0107] Comparative Example 1-2 provides a sodium ion battery positive electrode material, which is the same as Example 1 except that the conditions in Table 1 are different from those in Example 1.
[0108] Comparative Example 3-4 provides a sodium ion battery positive electrode material, which is the same as Example 1 except that the conditions of Table 1 in Example 1 are different, and the primary sintering temperature of Comparative Example 3 and the primary sintering time of Comparative Example 4 are changed, the primary sintering temperature of Comparative Example 3 is 800°C, and the primary sintering time of Comparative Example 4 is 8h.
[0109] Table 1 of the present invention shows the sodium doping amount, transition metal doping amount, coating amount, D1, D2, B1, B2, D2 / D1+B1×B2, I(003) / I(104), V and I(003) / I(104)×V of all embodiments and comparative examples of the present invention. 1 / 2 ; Among them, the sodium doping amount refers to the doping amount of the sodium dopant in the amount of the precursor material added, the transition metal doping amount refers to the doping amount of the transition metal dopant in the amount of the precursor material added, and the coating amount refers to the coating agent in the amount of the sintered material added.
[0110] Table 1
[0111]
[0112] The sodium ion battery positive electrode materials described in the above embodiments and comparative examples were tested for residual alkali content by an acid-base titration method, that is, the sodium carbonate content and the sodium hydroxide content.
[0113] The sodium ion battery positive electrode material, acetylene black and PVDF described in the above embodiments and comparative examples were weighed in a mass ratio of 94:3:3, mixed evenly, and then N-methylpyrrolidone was added. The mixture was stirred at 2000 rpm for 8 min using a homogenizer to form a viscous slurry. The mixture was evenly coated on an aluminum foil and then vacuum-baked at 80°C. The dried electrode was rolled and finally cut into a positive electrode sheet with a diameter of 14 mm, wherein the electrode sheet surface density was 9 mg / cm 2 , pole piece compaction 3.2g / cm 3 , then use a pure sodium sheet with a diameter of 15 mm as the negative electrode, Tianci ENA18 as the electrolyte, and a Whatman glass fiber diaphragm to assemble a sodium ion battery in an argon-filled glove box.
[0114] The sodium ion battery prepared as above was subjected to electrochemical performance tests, wherein the charge and discharge regime: voltage range was 2-4.05V, constant temperature test was performed at 25°C; cycle test: at 2.0-4.05V, 0.5C charge, 1.0C discharge for 50 cycles; capacity test: 0.1C charge, 0.1C discharge, and the first cycle charge and discharge efficiency was obtained; energy efficiency: energy efficiency at 2.0-4.05V, 0.5C charge / 1C discharge for 50 cycles.
[0115] The first charge and discharge diagram of the battery prepared from the sodium ion battery positive electrode material of Example 1 and Example 15 of the present invention is as follows Figure 1 As shown in the figure, the cycle retention rate comparison is as follows Figure 2 As shown in the energy efficiency cycle comparison diagram Figure 3 As shown by Figure 1-Figure 3 It can be seen that the performance of the battery obtained by the sodium ion battery positive electrode material described in Example 1 of the present invention is significantly improved compared with Example 15.
[0116] The test results are shown in Table 2:
[0117] Table 2
[0118]
[0119] From Table 1 and Table 2, we can see that:
[0120] (1) It can be seen from Examples 1-7 and Examples 14-15 that the positive electrode material of the sodium ion battery prepared by the present invention is a quaternary positive electrode material, and its precursor material includes a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside, so that the positive electrode material is a ternary nickel-iron-manganese with high nickel content inside and a quaternary nickel-iron-manganese-copper positive electrode material with low nickel content and high copper content outside, so that the sodium ion battery has both high capacity and excellent cycle performance; It can be seen from Example 1 and Comparative Example 1 that the present invention not only dopes at the transition metal site, but also dopes at the sodium site, which reduces the damage to the structure during the sodium ion insertion and extraction process, and is beneficial to improving the cycle performance of the battery; It can be seen from Example 1 and Comparative Example 2 that the present invention also performs coating, which not only improves the material stability, but also reduces the residual alkali content on the surface of the material; It can be seen from Example 1 and Comparative Examples 3-4 that the I(003) / I(104)×V 1 / 2 Outside the specific scope of the present invention, it indicates that the cation mixing of the material is relatively serious, or the interlayer spacing is small, resulting in low product capacity and poor circulation.
[0121] (2) It can be seen from Example 1 and Examples 8-11 that the amount of doping and coating in the present invention is preferably within a specific range, which is beneficial to further promote the improvement of battery performance; It can be seen from Example 1 and Examples 12-13 that D2 / D1+B1×B2 in the present invention is preferably within a specific range, so that the particle size and specific surface area of the positive electrode material can be effectively controlled by controlling the specific surface area and particle size of the precursor, and then the electrochemical properties of the positive electrode material can be effectively controlled, thereby controlling the internal crystal parameter performance of the material through the apparent physical and chemical properties, thereby achieving the purpose of effectively improving the performance of the positive electrode material of the sodium ion battery.
[0122] In summary, the present invention provides a sodium ion battery positive electrode material, a preparation method thereof, and a sodium ion battery. The sodium ion battery positive electrode material satisfies a specific relationship between the peak intensity ratio of the (003) crystal plane and the (104) crystal plane and the positive electrode material unit cell volume V, thereby ensuring the basic parameters of the sodium ion positive electrode product material, reducing the mixing phenomenon and improving the problem of small interlayer spacing, thereby effectively ensuring that the sodium ion battery positive electrode material exerts the optimal performance.
[0123] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery includes a ternary nickel-iron-manganese positive electrode material with high nickel content inside and a quaternary nickel-iron-manganese-copper positive electrode material with low nickel content and high copper content outside, and the positive electrode material of the sodium ion battery also includes a transition metal doping element, a sodium doping element and a coating element; The I(003) / I(104) of the sodium ion battery positive electrode material and the unit cell volume V of the sodium ion battery positive electrode material satisfy the following relationship: 14≤I(003) / I(104)×V 1 / 2 ≤22; The I(003) / I(104)≥1.2, 122Å 3 ≤V≤128Å 3 ; The sodium ion battery positive electrode material and the precursor material for preparing the sodium ion battery positive electrode material satisfy the following relationship: 10≤D2 / D1+B1×B2≤28; Wherein, D1 is the particle size D50 of the precursor material for preparing the positive electrode material of the sodium ion battery, B1 is the specific surface area of the precursor material for preparing the positive electrode material of the sodium ion battery, D2 is the particle size D50 of the positive electrode material of the sodium ion battery, and B2 is the specific surface area of the positive electrode material of the sodium ion battery; The D1 is 3.0-7.0 μm, and the B1 is 25-50 μm. 2 / g, D2 is 5.0-10.0 μm, and B2 is 0.3-0.7 μm 2 / g.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that The precursor material for preparing the sodium ion battery positive electrode material includes a ternary nickel-iron-manganese precursor with high nickel content inside and a quaternary nickel-iron-manganese-copper precursor with low nickel content and high copper content outside; And / or, the tap density of the precursor material for preparing the sodium ion battery positive electrode material is T1, and T1 is 1.0-1.6 g / cm 3 ; And / or, the tap density of the sodium ion battery positive electrode material is T2, and T2 is 1.9-2.3 g / cm 3 ; And / or, the chemical formula of the precursor material for preparing the sodium ion battery positive electrode material is Ni x Fe y Mn z Cu 1-x-y-z (OH)2 or Ni x Fe y Mn z Cu 1-x-y-z CO2, where 0.2≤x≤0.3, 0.3≤y≤0.4, 0.3≤z≤0.4, 0.85≤x+y+z≤0.95; And / or, the transition metal doping element includes any one or a combination of at least two of Al, Y, Ti, Ta, Zn, Zr, Sr, Sb, W, Mo, Nb or Co; And / or, the sodium-site doping element includes any one or a combination of at least two of Li, K, Ca, Mg, B or Sc; And / or, the coating element includes any one or a combination of at least two of Al, Y, Ti, Ta, Zn, Zr, Sr, Sb, W, Mo, Nb, Co, Ca, B or Mg.
3. A method for preparing a positive electrode material for a sodium ion battery as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a precursor material, a sodium source, a first dopant, and a second dopant once and sintering once to obtain a sintered material; The first dopant includes a transition metal doping element, and the second dopant includes a sodium doping element; (2) The calcined material and the coating agent in step (1) are mixed and sintered for a second time to obtain the positive electrode material for a sodium ion battery.
4. The preparation method according to claim 3, characterized in that: The first-burned material in step (1) is also crushed before the second mixing; And / or, the amount of the first dopant added in step (1) is 1000-10000 ppm of the amount of the precursor material added; And / or, the amount of the second dopant added in step (1) is 500-5000 ppm of the amount of the precursor material added; And / or, the primary sintering temperature in step (1) is 850-1050°C and the sintering time is 10-14h; And / or, the primary sintering in step (1) is carried out in an air atmosphere with a flow rate of 15-25 L / min.
5. The preparation method according to claim 3 or 4, characterized in that: The method for preparing the precursor material in step (1) comprises the following steps: The first mixed metal salt solution, the precipitant solution and the complexing agent solution are subjected to a first coprecipitation reaction, and after the first coprecipitation reaction is completed, the second mixed metal salt solution, the precipitant solution and the complexing agent solution are subjected to a second coprecipitation reaction to obtain the precursor material; The first mixed metal salt solution includes Ni ions, Fe ions and Mn ions, and the second mixed metal salt solution includes Ni ions, Fe ions, Mn ions and Cu ions.
6. The preparation method according to claim 5, characterized in that: When the amount of the first mixed metal salt solution added is 60-70% of the total amount, the first coprecipitation reaction is completed, and the copper salt solution is added to the remaining first mixed metal salt solution to obtain the second mixed metal salt solution; And / or, the temperature of the first coprecipitation reaction and the second coprecipitation reaction are independently 40-70° C., and the pH is independently 9-12; And / or, the total time of the first coprecipitation reaction and the second coprecipitation reaction is 12-24h.
7. The preparation method according to claim 3 or 4, characterized in that: The amount of the coating agent added in step (2) is 1000-10000ppm of the amount of the calcined material added; And / or, the secondary sintering temperature in step (2) is 600-800°C and the time is 8-12h; And / or, the secondary sintering in step (2) is carried out in an air atmosphere with a flow rate of 15-25 L / min.
8. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode material as claimed in claim 1 or 2.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as precursor, preparation method and application thereof
CN116314731A
Double-point-location doped sodium battery positive electrode material and preparation method and application thereof
CN116885140A